Understanding Mental Causation - White, Andrea (White Rose University Press, 2024)
Understanding Mental Causation proposes a new, non-relational theory of mental causation. Andrea White believes that contemporary philosophy of mind labours under a misapprehension of what mental causation is supposed to be. This volume explains where the leading theories go astray, and how the new theory proposed solves critical problems for philosophers of mind and action. Ordinary experience suggests that what we do with our bodies causally depends, somehow, on what is going on in our minds. However, the problem of how to understand the causal relationship between mind and body remains. Contemporary philosophy of mind is shaped by the question: how is it possible for the mental to causally interact with the physical? Mental causation is often presented as a cause-effect relation between mental and physical entities. This understanding of mental causation is widely endorsed because it seems like a straightforward explanation of what is going on when people act intentionally. Desires and beliefs are seen as causes of the actions they explain, entailing the existence of causal relations between mental items and physical events. White calls this the 'causalist' view of intentional action. This view is not universally accepted. The 'non-causalist' view denies that intentional action entails the existence of causal relations between mental items and physical events. However, non-causalists reach this conclusion by arguing that explanations of intentional actions which cite beliefs or desires are not usually causal explanations at all. White presents a theory of intentional action that falls between the 'causalist' and 'non-causalist' views. She rejects the idea that as-a-cause is how we should understand the place of mentality in intentional action. Concepts like belief, desire and intention do not refer to items which can stand in causal relations to actions or physical events. However, like causalists, she holds that explanations of intentional actions which cite the agent's thoughts do give causal information. This intermediary view demands a new theory about the causation that is on display when human beings act intentionally, one that does not reduce mental causation to a relation between mental items and physical events. Orthodox theories of causation, inspired by David Hume, assume that causation is always a relation between events. Therefore, the causation demonstrated in intentional action must be a relation, because all causation is, and will count as mental causation if and only if at least one of the terms of that relation is a mental entity. White challenges this orthodoxy by presenting her own non-relational theory of causation. Denying causation is always a relation, she holds instead that causation is a general type of process in which substances engage and that exercising a causal power is to engage in a process. White shows how this novel theory can be used to provide a better understanding of intentional action and the mental causation associated with it. She suggests that to act intentionally is to engage in a process and, as such, to exercise a power - but a power of a special sort. The power to act intentionally is a power to structure one's own activities so that they demonstrate a pattern - a pattern which is only revealed by attributing mental states to the agent. So, when an agent acts intentionally, they engage in the process of mental causation because the agent is manifesting a special power to organise their activities into a pattern that can be made sense of by appeal to mental concepts. Broadening our understanding of causation, and more specifically incorporating the concepts 'power' and 'process', opens up new ways of understanding intentional action and mental causation. In Understanding Mental Causation, White presents a compelling new account in this key area of philosophy of mind.